HUBUNGAN ANTARA STRES EMOSI DENGAN KUALITAS TIDUR LANSIA DI PANTI LKS.LU BERINGIN KABUPATEN GORONTALO PROVINSI GORONTALO - Hamna Lasanuddin; Firmawati Firmawati; Meigi Harun (Termometer: Jurnal Ilmiah Ilmu Kesehatan dan Kedokteran, 2023)
One of the impacts which is often experienced by the elderly is sleep disturbances, including sleep quality. The sleep quality of elderly is influenced by several factors, one of which is emotional stress. The Objective of research was to determine the relationship between emotional stress and quality of sleep on the elderly at the LKS.LU Beringin, Gorontalo Regency m The design uses a cross sectional research design. The population were all elderly at the Lks.Lu Beringin. The sample is 40 respondents. The sampling technique is purposive sampling. The research instrument used a questionnaire. The results showed 23 respondents had high emotional stress with poor sleep quality, while 14 respondents had low emotional stress with good sleep quality and 3 respondents had low emotional stress with poor sleep quality. Conclusion, there is a significant relationship (p value = 0.000) between emotional stress and quality of sleep for the elderly at the LKS.LU Beringin. Suggestions for the management of the orphanage can be used as input material in controlling the emotional stress of the elderly which can cause disturbances in the quality of sleep of the elderly.